Effective dissecting range and prognostic significance of lateral pelvic lymph node dissection for middle-low rectal cancer patients with lateral pelvic lymph node metastasis: Results of a large multicenter lateral node collaborative group in China - Zhou, Sicheng; Tang, Jianqiang; Liang, Jianwei; Lou, Zheng; Fu, Wei; Feng, Bo; Yang, Yingchi; Xiao, Yi; Liu, Qian (Frontiers in Oncology, 2022)
Background: Lateral pelvic lymph node (LPN) metastasis causes increased lateral local recurrence and poor prognosis. We aimed to investigate the prognostic significance and effective range of dissection for the LPN dissection (LPND) in rectal cancer patients with LPN metastasis. Materials and Methods: Through this large, multicenter retrospective cohort study, we evaluated the therapeutic effect of LPND. From January 2012 to December 2019, 387 rectal cancer patients with clinical evidence of LPN metastasis who underwent total mesorectal excision with LPND were included in the study. According to pathological findings, they were divided into negative (n = 296) and positive (n = 91) LPN groups. Primary endpoints were 3-year overall survival (OS), recurrence-free survival (RFS), and local recurrence-free survival (LRFS). Results: The OS, RFS, and LRFS in the positive group were significantly worse than those in the negative group; However, LPN metastases were not independent prognostic risk factors for LRFS (hazard ratio [HR]: 2.42; 95% confidence interval [CI], 0.77–7.64; P=0.132). Among patients with pathological LPN metastases, LPN metastases to the common and external iliac arteries were independent prognostic risk factors both for OS (HR: 4.74; 95% CI, 1.74–12.90; P=0.002) and RFS (HR: 2.70; 95% CI, 1.16–6.29; P=0.021). No significant difference was observed in the 3-year OS (72.3% vs. 70.2%, P=0.775) and RFS rates (60.9% vs. 52.6%, P=0.408) between patients with metastases to the obturator or internal iliac arteries and patients at N2b stage. Conclusions: LPND may be effective in controlling local recurrence in patients with LPN metastasis but not systemic metastases. Patients with LPN metastasis limited to the internal iliac and obturator regions achieve a long-term survival benefit from LPND, and their prognoses may be comparable to those at the N2b stage. Further metastasis to the external iliac or common iliac region should be considered systemic disease, and LPND should be avoided.